Development and evaluation of a simple and easy high‐performance liquid chromatography–ultraviolet system simultaneously suitable for determination of 24 anti‐epileptic drugs in plasma. Issue 13 (26th April 2022) - Zhao, Yan‐lin; Zhao, Lin‐lin; you, Yu‐xin; Zheng, Xiao‐xiao; Du, Yan; Tang, Dao‐quan
Abstract : We aim to establish a simple and easy high‐performance liquid chromatography system coupled with an ultraviolet detector suitable for simultaneous determination of 24 antiepileptic drugs in human plasma. Optimized chromatographic separation was performed on a ZORBAX Eclipse Plus‐C18 (4.6 × 150 mm 2, 3.5 μm) column with acetonitrile and 5 mM potassium dihydrogen phosphate water solution as mobile phase. Note that, 24 antiepileptic drugs were divided into three groups and eluted with different gradient procedures, respectively. The column temperature was maintained at 35°C and the detection wavelength was set at 210 nm. Plasma was processed with ethyl acetate or acetonitrile. The calibration curves of 24 antiepileptic drugs demonstrated good linearity within the test range ( r > 0.996). The intra‐ and inter‐batch precision and accuracy were all less than 15%, while extraction recoveries were in the range of 74.57–90.89% with the relative standard deviation values less than 15%. The validated methods have been successfully applied to determination of some antiepileptic drugs in rat or patient plasma. Those results indicated that the developed methods were simple and easy, and could be suitable for the determination of 24 antiepileptic drugs in plasma just by changing the gradient elution procedures of mobile phase.